2022
DOI: 10.3390/brainsci12060736
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Achievements in Mathematics on Cognitive Ability in Primary School

Abstract: Cognitive skills predict academic performance, so schools that try to improve academic performance might also improve cognitive skills. The purpose of this study was to determine the effect of achievements in mathematics on cognitive ability in primary school. Methods: Participants: 100 girls and 102 boys aged 9–10 years (the fourth grade) were selected from three schools. A diagnostic test of cognitive abilities (DTCA) was created by the authors of the article for the assessment of primary school students’ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The results of interviews with teachers and students also indicated that the teacher's competence (knowledge) which was transferred to students never exceeded the competence possessed by the teacher. This shows that teacher competence is actualized in learning mathematics in the classroom, where the teacher is a learning model for students, so their success is reflected in students' mathematics learning outcomes (Kliziene et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…The results of interviews with teachers and students also indicated that the teacher's competence (knowledge) which was transferred to students never exceeded the competence possessed by the teacher. This shows that teacher competence is actualized in learning mathematics in the classroom, where the teacher is a learning model for students, so their success is reflected in students' mathematics learning outcomes (Kliziene et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…The assessment criteria in the test are specific and individualized, making it an objective tool for determining learners' strengths and weaknesses to plan appropriate teaching and learning methods. Kliziene et al (2022) opine that the primary objective of the test is to measure changes in learners' knowledge, understanding, application of knowledge, and higher-order thinking skills. The test comprises tasks that reflect nine cognitive functions.…”
Section: Rationale For the Ca Diagnostic Testmentioning
confidence: 99%
“…Учасниками дослідження, відібраними з трьох шкіл, стали 100 дівчат і 102 хлопчики віком 9-10 років. Згідно з даними дослідження Kliziene et al (2022), діагностичний тест КЗ для математики в 4 класі ґрунтується на теорії динамічної оцінки когнітивної модальності Фойєрштайна та Левін-Бенхам, а також Загальній програмі початкової освіти, затвердженій міністром освіти та науки Литви (ISAK-2433(ISAK- , 2008. Цей тест, призначений для учнів 4-го класу, охоплює математику.…”
Section: Conflict Of Interestunclassified
See 1 more Smart Citation
“…The problem faced by students while learning mathematics is that they did not own the capability to make a connection between what they have learned and how the knowledge will be used in the future (Li & Schoenfeld, 2019). This assumption arises because the practice of mathematics learning in the classroom has several weaknesses, including (a) the mathematics learning focuses only on procedural knowledge so that it distracts the comprehensive understanding of mathematical concepts (Kusumadewi & Kusmaryono, 2022); (b) mathematics learning is limited by rigid completion procedures, causing students to be incapable to critically create their own ideas and construct their own knowledge (Otte, et al, 2019); (c) mostly the learning follows teacher-centered model, restricts students' independence to have active engagement in emotion, cognitive and behaviors, and also inhibits critical and creative thinking attitudes (Dyment, et al, 2018); (d) presenting examples of mathematical problems that are not in the context of life so that it is difficult for students to understand (Dyment, et al, 2018;Otte, et al, 2019); (e) the learning is not fun, boring, high pressured and stressed for students (Prasetya, et al, 2020); and (6) learning only has a short-term impact, where students are proficient in memory skills but weak in understanding mathematical concepts (Kliziene, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%